Perhitungan Rerating Motor Induksi Akibat Tegangan Tidak Seimbang Dengan Metode William - Darmansyah Darmansyah (UIN Sultan Syarif Kasim Riau, 2012)
Three-phase induction motor is one of the electric motor is in operation requires three-phase supply voltage is balanced to operate optimally. Three-phase supply voltages are un balanced can reduce the rating of the three-phase induction motor during operation.To calculate the rerating three-phase induction motor output due to supply voltage three-phase unbalanced done using the method of William. Unbalanced three-phase voltage obtained by simulation. Simulation is used Monte Carlo simulations to present three-phase induction motor condition with input voltages to the stator is unbalanced using the software MATLAB 7.The results of calculations show the influence of unbalanced input voltage by a factor of 0.76% voltage imbalance – 8.41% of a three-phase induction motor rating can be seen in the form of a decrease in the power rating of three-phase induction motor 10 hp to 9.45 – 4.03 hp.Keywords: rerating, Monte Carlo simulation, Method of William